2015
DOI: 10.1007/s10750-015-2403-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of niche conservatism and host fidelity in the polar shrimp Lebbeus kiae n. sp. (Decapoda: Caridea: Thoridae) from the Ross Sea, Antarctica

Abstract: We report a remarkable case of ‘bipolarism’, where two different polar species, namely Lebbeus polaris in the northern hemisphere and Lebbeus kiae n. sp., here described from the Southern Ocean, have been found to share similar ecologies. Despite the great geographical distance between the two species, both show high host fidelity in associations\ud with two congeneric sea anemones: Bolocera tuediae and Bolocera kerguelensis, respectively. A close molecular phylogenetic relationship between the two Lebbeus spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Lebbeus uschakovi may therefore be a specialized species, adapted to particular conditions of hard bottom biotopes with strong near bottom currents and rich epifauna. Taking into account ability of Lebbeus species to form association with cnidarians [Jonsson et al, 2001;Schiaparelli et al, 2015] we can't exclude that L. uschakovi also maintains commensal or symbiotic relationships with some epifaunal taxa. Effective collect-ing of Lebbeus species which have specialized modes of life requires targeted sampling (as partly applied in the present study) and even special methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lebbeus uschakovi may therefore be a specialized species, adapted to particular conditions of hard bottom biotopes with strong near bottom currents and rich epifauna. Taking into account ability of Lebbeus species to form association with cnidarians [Jonsson et al, 2001;Schiaparelli et al, 2015] we can't exclude that L. uschakovi also maintains commensal or symbiotic relationships with some epifaunal taxa. Effective collect-ing of Lebbeus species which have specialized modes of life requires targeted sampling (as partly applied in the present study) and even special methods, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Effective collect-ing of Lebbeus species which have specialized modes of life requires targeted sampling (as partly applied in the present study) and even special methods, i.e. remotely operated vehicles [Nye, Copley, 2014;Schiaparelli et al, 2015] or whale-bone mooring [Nye, 2013], because their biotopes may be difficult for applying conventional gears.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, in this work we reduced the effect of this issue by weighting the centroids and covariances of the ellipsoids of both modeling units to prevent that species with a higher density of records from skewing the models towards these conditions. 2) Even though niche conservatism is a widely observed pattern in marine species Warren et al 2008;Holland y Zaffos 2011;Schiaparelli et al 2015), there is also evidence of some exceptions in this environment. For example, Borza et al (2021) observed niche differentiation in different species of marine crustaceans.…”
Section: Discussionmentioning
confidence: 99%